M6A reader protein YTHDF2 regulates spermatogenesis by timely clearance of phase‐specific transcripts. Issue 1 (30th November 2021) - Qi, Meijie; Sun, Haifeng; Guo, Yueshuai; Zhou, Yu; Gu, Xueying; Jin, Jiachuan; Chen, Xiaoxu; Wang, Fangzhu; Ma, Honghui; Guo, Xuejiang; Chen, Hao; Shen, Bin
Abstract: Objectives: Accumulating evidences show that the regulatory network of m 6 A modification is essential for mammalian spermatogenesis. However, as an m 6 A reader, the roles of YTHDF2 remain enigmatic due to the lack of a proper model. Here, we employed the germ cell conditional knockout mouse model and explored the function of YTHDF2 in spermatogenesis. Materials and methods: Ythdf2  germ cell conditional knockout mice were obtained by crossing Ythdf2 ‐floxed mice with Vasa ‐ Cre and Stra8 ‐ Cre mice. Haematoxylin and eosin (HE) staining, immunofluorescent staining and Western blotting were used for phenotyping. CASA, IVF and ICSI were applied for sperm function analysis. RNA‐seq, YTHDF2‐RIP‐seq and quantitative real‐time PCR were used to explore transcriptome changes and molecular mechanism analysis. Results: Our results showed that YTHDF2 was highly expressed in spermatogenic cells. The germ cell conditional knockout males were sterile, and their sperm displayed malformation, impaired motility, and lost fertilization ability. During differentiated spermatogonia transiting to pachytene spermatocyte, most m 6 A‐modified YTHDF2 targets that were degraded in control germ cells persisted in pachytene spermatocytes of Ythdf2 ‐vKO mice. These delayed mRNAs were mainly enriched in pathways related to the regulation of transcription, and disturbed the transcriptome of round spermatid and elongated spermatid subsequently. Conclusion: Our data demonstrate that YTHDF2 facilitates the timely turnover of phase‐specific transcripts to ensure the proper progression of spermatogenesis, which highlights a critical role of YTHDF2 in spermatogenesis. Abstract : YTHDF2 accelerates the degradation of m 6 A‐modified RNA during the early stages of spermatogenesis. The timely clearance of phase‐specific transcripts mediated by YTHDF2 ensures the formation of functional sperm.